Development of egg PC/cholesterol/alpha-tocopherol liposomes with ionic gradients to deliver ropivacaine - Goncalves da Silva, Camila Morais; Fraceto, Leonardo Fernandes [UNESP]; Franz-Montan, Michelle; Couto, Veronica Muniz; Casadei, Bruna Renata; Saia Cereda, Cintia Maria; Paula, Eneida de (Taylor & Francis Ltd, 2016)
Context: Ropivacaine (RVC) is an aminoamide local anesthetic widely used in surgical procedures. Studies with RVC encapsulated in liposomes and complexed in cyclodextrins have shown good results, but in order to use RVC for lengthy procedures and during the postoperative period, a still more prolonged anesthetic effect is required.Objective: This study therefore aimed to provide extended RVC release and increased upload using modified liposomes.Materials and methods: Three types of vesicles were studied: (i) large multilamellar vesicle (LMV), (ii) large multivesicular vesicle (LMVV) and (iii) large unilamellar vesicle (LUV), prepared with egg phosphatidylcholine/cholesterol/-tocopherol (4:3:0.07mol%) at pH 7.4. Ionic gradient liposomes (inside: pH 5.5, pH 5.5+(NH4)(2)SO4 and pH 7.4+(NH4)(2)SO4) were prepared and showed improved RVC loading, compared to conventional liposomes (inside: pH 7.4).Results and discussion: An high-performance liquid chromatography analytical method was validated for RVC quantification. The liposomes were characterized in terms of their size, zeta potential, polydispersion, morphology, RVC encapsulation efficiency (EE(%)) and in vitro RVC release. LMVV liposomes provided better performance than LMV or LUV. The best formulations were prepared using pH 5.5 (LMVV 5.5(in)) or pH 7.4 with 250mM (NH4)(2)SO4 in the inner aqueous core (LMVV 7.4(in)+ammonium sulfate), enabling encapsulation of as much as 2% RVC, with high uptake (EE(%) approximate to 70%) and sustained release (approximate to 25h).Conclusion: The encapsulation of RVC in ionic gradient liposomes significantly extended the duration of release of the anesthetic, showing that this strategy could be a viable means of promoting longer-term anesthesia during surgical procedures and during the postoperative period.
Keywords: Drug delivery; encapsulation efficiency; sustained release